2019
DOI: 10.1108/jbs-11-2018-0191
|View full text |Cite
|
Sign up to set email alerts
|

Mission statements: what university research parks tell us about timing

Abstract: Purpose Mission statements are a key element of any organization. Ideally, the mission statement should be written at the initial stages of an organization’s life to be a useful tool to guide future organization’s decisions and strategy. However, at the early stages of an organization’s life, the organization might still be under development with the objective and stakeholders not yet well-defined, and therefore, stating the mission so early on, might neglect some important elements. In this paper, the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…According to the Association of University Science Parks (AURP, 2021), the main idea is to generate, attract and maintain research institutions and talents in line with sponsoring research institutions, which include universities, public and private research laboratories. Information flows from academia to the business sector are rapidly taking place in geographically close regions and they are an essential tool for creating innovation (Alegre et al, 2019). At the same time, they bridge the gap between the supply of universities and the private sector on the demand side, requiring the knowledge and expertise of universities (Leyden et al, 2008).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…According to the Association of University Science Parks (AURP, 2021), the main idea is to generate, attract and maintain research institutions and talents in line with sponsoring research institutions, which include universities, public and private research laboratories. Information flows from academia to the business sector are rapidly taking place in geographically close regions and they are an essential tool for creating innovation (Alegre et al, 2019). At the same time, they bridge the gap between the supply of universities and the private sector on the demand side, requiring the knowledge and expertise of universities (Leyden et al, 2008).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Kosm€ utzky and Kr€ ucken (2015) investigated the similarities and differences in universities based on mission statements. Similarly, Alegre et al (2019) studied the mission statements and the strategy of research parks and concluded that the mission statement is an effective strategic tool aimed at achieving objectives and promoting the development of strategic plans to meet established goals based on institutional values.…”
Section: Differentiation Of Colombian University 1421mentioning
confidence: 99%